Protecting workers from violence and abuse: a union rep's guide - Oates, Andrea (London, 2017)
"he UK has some of the highest levels of work-related violence in Europe and while the workers most at risk are those in contact with people from outside their organisation, violence and abuse can happen in any workplace. Union reps and safety reps have a key role to play in ensuring that employers provide suitable levels of protection for their workers. This LRD booklet provides practical guidance on how to prevent or reduce work-related violence and abuse, as well as giving advice on what action to take when it does occur. Crucially, it explains how reps can use the law to persuade employers to take action to prevent violence at work. This booklet also provides practical examples showing how unions and reps across a range of sectors and in a variety of workplaces have tackled workplace violence and abuse"